METHODOLOGY FOR THE DEVELOPMENT OF SANOGEN THINKING IN STUDENTS BASED ON HISTORICAL MATERIALS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Sanogen thinking, as a mental health-oriented approach, plays a vital role in developing students' critical and creative thinking abilities. This article explores the methodology of developing sanogen thinking in students through the use of historical materials. The study analyzes various historical events, personalities, and scenarios to illustrate how sanogen thinking can be fostered. The proposed methodology includes a structured approach that integrates critical analysis, emotional reflection, and creative synthesis, providing students with tools to overcome stress and enhance cognitive flexibility.